Soluble Epstein-Barr Virus Glycoproteins gH, gL, and gp42 Form a 1:1:1 Stable Complex That Acts Like Soluble gp42 in B-Cell Fusion but Not in Epithelial Cell Fusion - Kirschner, Austin N. (American Society for Microbiology, 2006)
Epstein-Barr virus (EBV) is a herpesvirus that infects cells by fusing its lipid envelope with the target cell membrane. The fusion process requires the actions of viral glycoproteins gH, gL, and gB for entry into epithelial cells and additionally requires gp42 for entry into B cells. To further study the roles of these membrane-associated glycoproteins, purified soluble forms of gp42, gH, and gL were expressed that lack the membrane-spanning regions. The soluble gH/gL protein complex binds to soluble gp42 with high affinity, forming a stable heterotrimer with 1:1:1 stoichiometry, and this complex is not formed by an N-terminally truncated variant of gp42. The effects of adding soluble gp42, gH/gL, and gH/gL/gp42 were examined with a virus-free cell-cell fusion assay. The results demonstrate that, in contrast to gp42, membrane fusion does not proceed with secreted gH/gL. The addition of soluble gH/gL does not inhibit or enhance B-cell or epithelial cell fusion when membrane-bound gH/gL, gB, and gp42 are present. However, the soluble gH/gL/gp42 complex does activate membrane fusion with B cells, similarly to soluble gp42, but it does not inhibit fusion with epithelial cells, as observed for gp42 alone. A gp42 peptide, derived from an N-terminal segment involved in gH/gL interactions, binds to soluble gH/gL and inhibits EBV-mediated epithelial cell fusion, mimicking gp42. These observations reveal distinct functional requirements for gH/gL and gp42 complexes in EBV-mediated membrane fusion.